PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DI WILAYAH KECAMATAN KEMANG KABUPATEN BOGOR - Sinta Dewi; Ahmad Nazir (Jurnal Menara, 2025)
This This study aims to analyze the influence of human resource (HR) quality and career development on employee performance in Kemang District, Bogor Regency, both partially and simultaneously. The research method uses a quantitative approach with saturated sampling technique, involving 60 respondents. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficients, determination coefficients, and hypothesis tests. The results of the study indicate that partially, HR quality has a positive and significant effect on employee performance (t count 4.314 > t table 2.001; sig. 0.000 < 0.05). Career development also has a positive and significant effect (t count 5.628 > t table 2.001; sig. 0.000 < 0.05). Simultaneously, HR quality and career development have a positive and significant effect on employee performance (F count 19.591 > F table 2.001; sig. 0.000 < 0.05). The regression equation obtained is Y = 3.832 + 0.238X₁+ 0.591X₂ with a coefficient of determination of 40.7%, while 59.3% is influenced by other factors outside the study. Thus, both partially and simultaneously, human resource quality and career development have a significant influence on employee performance.